2021
DOI: 10.35366/101743
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización genómica y variantes del virus SARS-CoV-2

Abstract: El SARS-CoV-2 es un nuevo tipo de coronavirus que posee un genoma de ARN monocatenario de sentido positivo, este virus se detectó por primera vez en diciembre de 2019 en la ciudad de Wuhan, China y causa la enfermedad que se denomina COVID-19. La tasa de mutación en los virus de ARN es extremadamente alta, el SARS-CoV-2 posee un mecanismo que corrige los errores en la replicación, por lo tanto, su tasa de mutación es menor. Sin embargo, a pesar de este mecanismo comete errores que generan un amplio espectro de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…As time elapsed, numerous SARS‐CoV‐2 variants have been discovered, which show genetic differences with respect to the wild‐type Wuhan's strain sequenced on 07 January 2020. These variants emerged as a result of spontaneous mutations in the viral RNA, proceeding from mistakes in its replication within the host cell 7,8 . Unlike other RNA viruses (influenza and HIV), coronaviruses have intrinsic mechanisms for repairing their mistakes that minimize mutability rates; hence, there is a high homology between the genomes of the different variants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As time elapsed, numerous SARS‐CoV‐2 variants have been discovered, which show genetic differences with respect to the wild‐type Wuhan's strain sequenced on 07 January 2020. These variants emerged as a result of spontaneous mutations in the viral RNA, proceeding from mistakes in its replication within the host cell 7,8 . Unlike other RNA viruses (influenza and HIV), coronaviruses have intrinsic mechanisms for repairing their mistakes that minimize mutability rates; hence, there is a high homology between the genomes of the different variants.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these mutations increased the adaptation capability of numerous SARS‐CoV‐2 variants in their hosts. This fact could lead to the virus being persistent and able to replicate and preserve itself afterwards 7 . With more than 2 million isolates of SARS‐CoV‐2 that have undergone partial or complete genomic sequencing, primitive data suggested that SARS‐CoV‐2 was exceptionally well adapted to human's body, and spreading rapidly with little evidence about natural selection among circulating viruses 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palavras-chave: Animais domésticos, doença do coronavírus 2019 (COVID- 19), síndrome respiratória aguda grave do coronavírus 2 (SARS-CoV-2), transmissão interespécies, variantes antigênicas.…”
Section: Introductionunclassified